Exciton efficiency beyond the spin statistical limit in organic light emitting diodes based on anthracene derivatives. Issue 11 (17th February 2020) - Sharma, Nidhi; Wong, Michael Yin; Hall, David; Spuling, Eduard; Tenopala-Carmona, Francisco; Privitera, Alberto; Copley, Graeme; Cordes, David B.; Slawin, Alexandra M. Z.; Murawski, Caroline; Gather, Malte C.; Beljonne, David; et al.
Abstract : We report two donor–acceptor (D–A) materials based on a cyanoanthracene acceptor paired with diphenylamine (DPAAnCN ) and carbazole (CzAnCN ) donor moieties. Abstract : We report two donor–acceptor (D–A) materials based on a cyanoanthracene acceptor paired with diphenylamine (DPAAnCN ) and carbazole (CzAnCN ) donor moieties. These compounds show hybrid locally excited (LE) charge-transfer (CT) excited states (HLCT), which we demonstrated through a combined photophysical and computational study. Vacuum-deposited organic light emitting diodes (OLEDs) using these HLCT emitters exhibit maximum external quantum efficiencies (EQEmax ) close to 6%, with impressive exciton utilization efficiency ( Φ s ) of >50%, far exceeding the spin statistic limit of 25%. We rule out triplet–triplet annihilation and thermally activated delayed fluorescence as triplet harvesting mechanisms along with horizontal orientation of emitters to enhance light outcoupling and, instead, propose a "hot exciton" channel involving the nearly isoenergetic T2 and S1 states.